Mixed dentition space analysis among Nepalese Brahmins/Chhetris. Issue 1 (December 2017) - Gyawali, Rajesh; Shrestha, Basanta; Yadav, Rajiv
Abstract Background Mixed dentition space analysis forms an important part of orthodontic diagnosis and treatment planning. Regression equations are widely used for mixed dentition analysis which can vary among races. This study aimed to find out the new regression equation in estimating the size of unerupted canines and premolars for Nepalese Brahmins/Chhetris. Methods Hundred Nepalese Brahmins/Chhetris (50 males and 50 females) who met our criteria were selected among the patients attending to the Orthodontic Out-Patient Department, Institute of Medicine, Kathmandu. The mesiodistal widths of all mandibular permanent incisors; maxillary and mandibular canines and premolars were measured and analyzed. The results were also compared with predicted values from the Moyers and the Tanaka and Johnston methods. Correlation and linear regression analyses were performed between the predicted and actual tooth sizes for Nepalese Brahmins/Chhetris and standard regression equations were developed. Results No significant differences were observed when the sum of canine and premolars of one quadrant is compared between sides and sex. Significant and high positive correlations were found between the mandibular incisors and the combined mesiodistal widths of the canines and premolars for the maxillary (r  = 0.72) and mandibular (r  = 0.73) segments. Significant differences were observed between the measured values from this study and from Moyers (50 % and 75 % probability) and Tanaka-Johnston methods. Conclusions The equations and charts commonly used for North American children (50th or 75th percentile) did not accurately predict for our sample, so new regression equations and tables were developed for Nepalese Brahmins/Chhetris children.